2011
DOI: 10.4314/ajpsy.v13i5.63103
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma in adults with social anxiety disorder and panic disorder: a cross-national study

Abstract: Objectives: The influence of childhood trauma as a specific environmental factor on the development of adult psychopathology is far from being elucidated. As part of a collaborative project between research groups from South Africa (SA) and Sweden focusing on genetic and environmental factors contributing to anxiety disorders, this study specifically investigated rates of childhood trauma in South African and Swedish patients respectively, and whether, in the sample as a whole, different traumatic experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
9
23
0
1
Order By: Relevance
“…Similarly, van der Vegt et al (2010) examined awakening cortisol levels in anxiety disorders, and stressed the effects of early childhood adversity on cortisol reactivity in these conditions. This is in keeping with the notion that emotional abuse (EA), more so than physical or sexual abuse, may be associated with the pathophysiology of SAD (Asher and Coie, 1990;Lochner et al, 2010). More recently, a study has found that different forms of CT are associated with different CSR (Kuhlman et al, 2015).…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similarly, van der Vegt et al (2010) examined awakening cortisol levels in anxiety disorders, and stressed the effects of early childhood adversity on cortisol reactivity in these conditions. This is in keeping with the notion that emotional abuse (EA), more so than physical or sexual abuse, may be associated with the pathophysiology of SAD (Asher and Coie, 1990;Lochner et al, 2010). More recently, a study has found that different forms of CT are associated with different CSR (Kuhlman et al, 2015).…”
Section: Introductionsupporting
confidence: 75%
“…This finding was driven by a negative association between emotional abuse scores and cortisol AUC G in the SAD group, which strongly contrasted the marked positive relationship between emotional abuse scores and AUC G in the control group. Past research has shown that individuals with SAD report higher rates of CT, and in particular EA, compared to healthy individuals (Asher and Coie, 1990;Lochner et al, 2010). The present findings suggest that EA in SAD patients is associated with an altered cortisol stress response, in particular total cortisol exposure in response to a social challenge as reflected in the AUC G .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Second, previous research has also found anxiety disorders to be associated with emotional traumas, that is, those traumas that do not stem from a physical act, e.g. being assaulted or being in an accident [44]. However, within this study, those in the high risk group, who were at the highest risk of the anxiety disorders examined, reported a wide variety of physical based traumas, ranging from being mugged to witnessing fights at home.…”
Section: Discussionmentioning
confidence: 40%
“…While much research has focused on the role that early life trauma plays in the development of anxiety disorders among children (Stein et al, 1996;Pynoos et al, 1999;Heim and Nemeroff, 2001;Hovens et al, 2010Hovens et al, , 2012Hovens et al, , 2015Lochner et al, 2010;Klauke et al, 2011;Kuo et al, 2011;Zikic et al, 2015), a growing body of studies suggest that the adverse effects of traumatic events as well as other stressors on the development of anxiety disorders in children may begin before birth (Yehuda et al, 2001;Najman et al, 2010;Rice et al, 2010;Davis and Sandman, 2012;Betts et al, 2014;Park et al, 2014). Researchers have hypothesized that excess exposure to maternal stress hormones during gestation plays a key role in fetal programming of offspring anxiety disorders via causing permanent alterations to hypothalamic-pituitary-adrenal (HPA) axis function and/or via contributing to epigenetic modifications that adversely shape offspring stress reactivity (Weaver et al, 2004;Skinner et al, 2008;Glover et al, 2010;Davis et al, 2011;Radtke et al, 2011;Perroud et al, 2014).…”
Section: Introductionmentioning
confidence: 99%